2011
DOI: 10.5267/j.ijiec.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Weibull data and autocorrelation on the performance of the Shewhart and exponentially weighted moving average control charts

Abstract: Many real-world processes generate autocorrelated and/or Weibull data. In such cases, the independence and/or normality assumptions underlying the Shewhart and EWMA control charts are invalid. Although data transformations exist, such tools would not normally be understood or employed by naive practitioners. Thus, the question arises, "What are the effects on robustness whenever these charts are used in such applications?" Consequently, this paper examines and compares the performance of these two control char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Table 3 shows that the residuals of all the three models are normally distributed (p-value ≥ 0.05). Hence the residuals can be monitored using a control chart (Jayathavaj & Pongpullponsak, 2014;Black et al, 2011).…”
Section: Case Studymentioning
confidence: 99%
“…Table 3 shows that the residuals of all the three models are normally distributed (p-value ≥ 0.05). Hence the residuals can be monitored using a control chart (Jayathavaj & Pongpullponsak, 2014;Black et al, 2011).…”
Section: Case Studymentioning
confidence: 99%
“…Thereafter, a number of researchers investigated the performance of parametric GWMA schemes, to count a few, Sheu and Yang (2006), Sheu and Hsieh (2009), Tai and Lin (2009), Teh et al (2012), Aslam et al (2017), Chakraborty et al (2017), etc. SPM schemes have been applied to a variety of fields, including engineering, production, manufacturing, finance, food industry, chemistry and biochemistry, see Simoglou et al (1997), Black et al (2011), Bag et al (2012), Lim et al (2017), etc. In practice, the underlying process distribution is generally unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, for conventional control charts including Shewhart charts, cumulative sum (CUSUM) charts, and exponentially weighted moving average (EWMA) charts, and deviations from either the distributional assumption and/or the uncorrelated assumption may result in either more frequent false alarms or reduced anomaly detection power. See, for example, Johnson and Bagshaw 3 and Black et al 4 There has been work in developing SPC methods for correlated observations under a normality assumption. Most methods are "residual-based" methods, where a model is assumed to describe the correlation structure within the data, and the approximately uncorrelated residuals are extracted for use in a control chart.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, for conventional control charts including Shewhart charts, cumulative sum (CUSUM) charts, and exponentially weighted moving average (EWMA) charts, and deviations from either the distributional assumption and/or the uncorrelated assumption may result in either more frequent false alarms or reduced anomaly detection power. See, for example, Johnson and Bagshaw and Black et al…”
Section: Introductionmentioning
confidence: 99%